2020
DOI: 10.1002/widm.1365
|View full text |Cite
|
Sign up to set email alerts
|

Continuous authentication using biometrics: An advanced review

Abstract: The shortcomings of conventional access control systems for high‐security environments have led to the concert of continuous authentication. Contrary to traditional verification, in which users are authenticated only once at the start of their session, continuous authentication systems regularly check users' identities to prevent hijackings. The challenges in this area involve balancing the security of protected assets by quickly detecting intruders with the system usability for genuine users. Biometric recogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 81 publications
1
37
0
Order By: Relevance
“…3(C)). The EERr was very similar for all the methods for channel lengths (3)(4)(5)(6)(7)(8). For a combination of TD with spectral features it was observed that TD+FDT and TD+AR had similar values in all the three scenarios and for different channel lengths (p>0.05).…”
Section: (A and B) The Median Auc And The Median Eer For The Three Feature Extraction Methods (Fdt Td And Ar) And Number Of Channels (1-8mentioning
confidence: 75%
See 3 more Smart Citations
“…3(C)). The EERr was very similar for all the methods for channel lengths (3)(4)(5)(6)(7)(8). For a combination of TD with spectral features it was observed that TD+FDT and TD+AR had similar values in all the three scenarios and for different channel lengths (p>0.05).…”
Section: (A and B) The Median Auc And The Median Eer For The Three Feature Extraction Methods (Fdt Td And Ar) And Number Of Channels (1-8mentioning
confidence: 75%
“…The TD method had a significantly lower R5E for 1-2 number of channels. However, for the inclusion of more channels (3)(4)(5)(6)(7)(8), there was no difference between the R5E for TD and FDT, but the AR had a significantly higher R5E than TD and FDT (p<0.05). For a combination of TD with spectral features it was observed that the R1E for TD+FDT was significantly lower (p<0.05) than the TD+AR and TD for different channel lengths.…”
Section: B Performance Evaluation Of Identification Systemmentioning
confidence: 89%
See 2 more Smart Citations
“…This allowed us to redefine the emission process of the HOrBAC digital parafer by proposing a version with in behaviour detection. The proposed detection algorithm can be used for continuous authentication [1,11]. Our approach resulted in a reduction of 89.12% of the deferred requests issued according to the experiment.…”
Section: Discussionmentioning
confidence: 96%